Dancing Improves Emotional Regulation in Women With Methamphetamine Use Disorder But Use of a Cycle Ergometer Does Not - Tao, Qian; Zhang, Chenping; Li, Xiawen (Frontiers in Neuroscience, 2021)
Background. Emotional regulation is crucial to people who receive a diagnosis of methamphetamine (MA) use disorder. Although evidence that exercise improves emotional regulation is robust, little is known about whether exercise will improve emotional processing in women with MA use disorder. Methods. In the present study, 36 women with MA use disorder aged 20 to 34 years and residing in the Drug Rehabilitation Bureau of Mogan Mountain in Zhejiang province were assigned to 1 of 2 exercise intervention groups-dancing or stationary cycling. Both types of exercise were performed at 65%-75% of the maximum heart rate for 30 min. Immediately before and after the exercise bout, the participants were asked to score their feelings using a 9-point Likert scale as they viewed emotionally negative, positive, or neutral images in blocks of 20 images each, for a total of 60 images. Concurrent with viewing the images and self-rating their emotions, the women also underwent functional near-infrared spectroscopy to assess changes in brain activity. Results. There were no significant differences in the demographic or MA use characteristics assessed for the women between the 2 exercise groups. We found main effect of image valence (F2,33=69.61, p<0.01), significant interaction effect of time and image valence was found (F2,33=4.27, p<0.05) and trend increase in the self-rated emotional scale score for viewing negative images in both groups after 30-min exercise intervention, and the dancing group presented more significant trends than cycling group. In addition, activation in the dorsolateral prefrontal cortex of dancers, but not of cyclists, while viewing negative images was significantly lower after vs. before dancing (F2,33=5.43, p<0.05). This result suggested that 30 min of dancing decreased neural activity in women with MA use disorder while they viewed negative images specifically in a brain region known to guide the selection of appropriate behaviors, and to shift attention. Taken together, the findings of this study suggest that for women with MA abuse disorder, 30 min of dancing, rather than of stationary cycling, may ameliorate negative emotional reactions by decreasing attention to negative stimuli.